2021
DOI: 10.1097/md.0000000000028234
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-associated parameters in patients with psoriasis

Abstract: Background: The relationship between platelet-associated parameters and psoriasis has been controversial. The purpose of our meta-analysis was to assess whether platelet count, platelet-to-lymphocyte ratio (PLR), mean platelet volume (MPV), and platelet distribution width (PDW) are associated with psoriasis.Methods: We performed a thorough documentation retrieval via PubMed, EMBASE, and Web of Science until June 2021. Pooled standardized mean differences (SMDs) and 95% confidence intervals (CIs) were calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…Our study extends the findings of a recent meta-analysis by Li et al (2021) of 22 studies including 3287 patients which found that higher MPV and PDW, but not PLT, were associated with presence of psoriasis [ 67 ]. The discrepancies between PLT and PDW conclusions between studies is likely attributable to differences in number of included studies; indeed, our meta-analyses were able to include all 22 studies reported by Li et al as well as an additional 11 relevant studies to investigate platelet indices in both presence and severity of psoriasis.…”
Section: Discussionsupporting
confidence: 90%
“…Our study extends the findings of a recent meta-analysis by Li et al (2021) of 22 studies including 3287 patients which found that higher MPV and PDW, but not PLT, were associated with presence of psoriasis [ 67 ]. The discrepancies between PLT and PDW conclusions between studies is likely attributable to differences in number of included studies; indeed, our meta-analyses were able to include all 22 studies reported by Li et al as well as an additional 11 relevant studies to investigate platelet indices in both presence and severity of psoriasis.…”
Section: Discussionsupporting
confidence: 90%
“…It was found that PLR, MPV and platelet distribution width were significantly higher in the patient group compared to the control group, which may indicate low-grade systemic inflammation and platelet activation in patients with psoriasis. 20 In some studies, NLR, PLR and MPV were found related or correlated with the disease severity or activity in adult psoriasis. [11][12][13]21 In our study, there was no significant correlation or relationship between PASI score and laboratory parameters in plaque type pediatric psoriatic patients.…”
Section: Discussionmentioning
confidence: 98%
“…Patients with psoriasis exhibit significantly increased platelet activation. 20 Platelets, in addition to their role in hemostasis, have multiple functions related to inflammation, immune responses, and endothelial damage that can contribute to the formation of atherosclerotic plaques or thrombotic complications. [21][22][23] In psoriasis, platelets play a crucial role in disease pathogenesis by activating leukocyte migration to the skin and releasing various pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 During immune-mediated inflammatory responses, activated platelets interact with leukocytes, leading to the release of a high concentration of cytokines, chemokines, and growth factors. 20,26 This platelet-leukocyte interaction and subsequent excessive release of cytokines and chemokines may trigger leukocyte infiltration into the skin, a hallmark feature of psoriasis. 27,28 Platelet activation and changes in platelet count, volume, and size, such as mean platelet volume and platelet distribution width, serve as indicators of platelet activation.…”
Section: Discussionmentioning
confidence: 99%